2021
DOI: 10.3389/fphys.2020.617041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aerobic and Muscular Power Between Junior/U23 Slalom and Sprint Paddlers: An Analysis of International Medalists and Non-medalists

Abstract: This study aimed to compare the aerobic power (treadmill running) and muscle power (bench press and bench pull) of Junior/U23 paddlers from Slovakia who won medals in international championships with that of those who did not take the podium. Forty-three Slovak Junior/U23 paddlers (sprint = 24, medalists = 8, non-medalists = 16; slalom = 19, medalists = 11, non-medalists = 8) were tested in 2018 and 2019 after the world championships. The maximal oxygen uptake (VO2max) and the velocity at maximal oxygen uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Bielik et al (2019) compared the power (paddling) and velocity (running) at maximum oxygen uptake (VO 2max ) from Slovakian medalists and non-medalists in Olympic games and observed considerable raw differences in Rio 2016 for paddling and London 2012 for running. The same group observed similar mean power on bench press/pull and velocity at VO 2max between medalists and nonmedalists in the 2018/2019 Junior/U23 European and World championships (Bielik et al, 2020) (Table 2). Vieira et al (2015) observed a moderate to strong inverse correlation between physiological parameters measured during (i.e., maximum, mean, and minimum heart rate) or after (i.e., blood lactate concentration peak) the simulated task and the race time, although this was not significant.…”
Section: Mechanical Variables and Slalom Performancementioning
confidence: 73%
See 4 more Smart Citations
“…Bielik et al (2019) compared the power (paddling) and velocity (running) at maximum oxygen uptake (VO 2max ) from Slovakian medalists and non-medalists in Olympic games and observed considerable raw differences in Rio 2016 for paddling and London 2012 for running. The same group observed similar mean power on bench press/pull and velocity at VO 2max between medalists and nonmedalists in the 2018/2019 Junior/U23 European and World championships (Bielik et al, 2020) (Table 2). Vieira et al (2015) observed a moderate to strong inverse correlation between physiological parameters measured during (i.e., maximum, mean, and minimum heart rate) or after (i.e., blood lactate concentration peak) the simulated task and the race time, although this was not significant.…”
Section: Mechanical Variables and Slalom Performancementioning
confidence: 73%
“…After the removal of duplicates (66 studies), 59 articles were checked at the title and abstract level, of which 38 were excluded. Finally, 21 full-texts were screened, and eight (Hunter et al, 2008 ; Messias et al, 2015 ; Vieira et al, 2015 ; Ferrari et al, 2017 ; Bielik et al, 2019 , 2020 ; Macdermid et al, 2019 ; Baláš et al, 2020 ) reached the eligibility criteria ( Figure 1 ). The eligible study's mean quality was high (92.9 ± 2.9%) and classified as having excellent methodological quality according to the 16-item checklist.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations